Theatralization of Alan Bennett’s Prose - Семейкина, Наталья Николаевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
Theatralization of prose is studied in modern science of literature as a poetical category and as a special means of inner organization of artistic text. In the prosaic works such as «The Uncommon Reader», «The Clothes They Stood Up», «The Greening of Mrs.Donaldson» written by the famous English modern dramatist Alan Bennett, theatralization is one of his main stylistic devices and the means of «sujetcomposition» and socio-phsychological characteristic of his heroes, it can also be understood as a space of game.